(untitled) (Research, Society and Development, 2025)
The objective of this article is to analyze the importance of science fairs in schools. It seeks to explore a universe full of discoveries, experiences, and reflections that go far beyond the simple act of presenting school projects, showing how science fairs can be powerful tools for developing essential skills in the lives of our young people. This is an integrative literature review. Data was collected from the SciELO and Google Scholar databases, considering works (articles, theses, and/or dissertations) published on the topic of Science Fairs in the year 2025. As a result, it can be mentioned that science fairs play an important role within the school context and, if conducted responsibly and with qualified professionals, can only contribute to improving the quality of student education, both inside and outside of school.